HUBUNGAN EFIKASI DIRI BIDANG AKADEMIK DAN PERILAKU BELAJAR DENGAN HASIL BELAJAR GEOGRAFI KELAS XI IS DI MAN 3 BANDA ACEH - Suriyani, Susi; Abdi, Abdul Wahab; Hasmunir, . (Universitas Syiah Kuala, 2017)
Self efficacy is very important in the daily life of students because it can build a sense of confidence, student motivation, and as a reflection of each individual about the ability to learn in every field of learning. Students with good or bad self efficacy can also influence students' behavior in the learning process. The problem formulation in this research is whether there is a significant correlation between self efficacy of academic field and learning behavior with learning result of class XI IS geography in MAN 3 Banda Aceh. In particular this study aims to determine the relationship between self-efficacy academic field and learning behavior with learning outcomes geography class XI IS in MAN 3 Banda Aceh. This research approach is a quantitative approach. The population of this study were students of MAN 3 Banda Aceh, while the sample in the study were students of class XI IS MAN 3 Banda Aceh. Based on data analysis, the findings of this study can be put forward as follows: the relationship between self-efficacy in the academic field (X1) and learning behavior (X2) with the learning outcomes of geography (Y) class XI IS in MAN 3 Banda Aceh is 0.136 very low. The correlation between self efficacy of academic field (X1), learning behavior (X2), and geography learning result (Y) has no significant relation with value of Fcount and Ftable ie 0,366 3,24. The conclusion of this research is that there is no significant correlation between self efficacy of academic field and learning behavior with learning result of class XI IS geography in MAN 3 Banda Aceh